2022
DOI: 10.3389/fcvm.2022.1045730
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue is associated with left atrial volume and fibrosis in patients with atrial fibrillation

Abstract: BackgroundObesity is a risk factor for atrial fibrillation (AF) and strongly influences the response to treatment. Atrial fibrosis shows similar associations. Epicardial adipose tissue (EAT) may be a link between these associations. We sought to assess whether EAT is associated with body mass index (BMI), left atrial (LA) fibrosis and volume.MethodsLA fibrosis and EAT were assessed using late gadolinium enhancement, and Dixon MRI sequences, respectively. We derived 3D models incorporating fibrosis and EAT, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Cardiac MR is currently considered the gold standard in imaging any type of adipose tissue because it has excellent spatial resolution but lacks the ionizing radiation hazards associated with CT. Recently, fat-water separation sequences (e.g., Dixon) proved valuable in detecting pericardial outlines and accurately quantifying EAT (12,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac MR is currently considered the gold standard in imaging any type of adipose tissue because it has excellent spatial resolution but lacks the ionizing radiation hazards associated with CT. Recently, fat-water separation sequences (e.g., Dixon) proved valuable in detecting pericardial outlines and accurately quantifying EAT (12,20).…”
Section: Discussionmentioning
confidence: 99%
“…It is also thought to secrete profibrotic factors like tumor growth factor β, matrix metalloproteinases, and activin A, all of which can induce fibrotic remodeling within the myocardial wall with a resultant electrical heterogeneity and local conduction block forming a substrate for AF (10,11). LA EAT was shown to correlate with fibrotic remodeling in the atrial wall (12).…”
Section: Introductionmentioning
confidence: 99%
“…Hearts of obese individuals and in preclinical models also show significant accumulation of lipid deposition in the myocardium and pericardium. 19 Evidence of increased cardiac fibrosis has been reported in obese patients and animal models, 18 , 20 although direct causation has not been clearly demonstrated. Below, we discuss mechanisms driving AF in obesity.…”
Section: Pathogenesis Of Af In Obesitymentioning
confidence: 99%
“… 26 Increased LA EAT volume also independently correlated with greater LA fibrosis and dilatation, which are predictors for AF. 19 Several preclinical studies demonstrate a significant role for EAT in AF pathogenesis (eg, via paracrine signaling) (see subsections Inflammation, Fibrosis, and Oxidative Stress; Neurohormonal Changes; and Electrical Remodeling).…”
Section: The Role Of Eat In Afmentioning
confidence: 99%
“… 9 , 10 Previous studies have revealed the association between LA EAT and LA volume based on cardiac magnetic resonance imaging in patients with AF. 11 However, there was no clear proof for the associations among atrial myopathy, LV diastolic function, and EAT volume.…”
mentioning
confidence: 99%